Heritage Conservation and Restoration (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The scope of this Special Issue was to collect together all the new research activities related to the research line (topic) and encourage researchers to read new research activities in one place. All these research studies will be helpful for finding out research innovations. Moreover, this reprint will provide easy access to collated articles for the readers.